Universities and University Libraries in Turkey - Kaygusuz, Ayhan (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
This article draws a picture of the education system and library environment in Turkey. It starts off with a brief overview of the Turkish education system and the proportion of the population involved in formal and informal education. As 44% of the Turkish population is under 25, there is a big demand for higher education in Turkey. This demand drives the authorities to open new universities and provide higher education for more young people. 54 new universities have been established since 2000. University librarians try to cope with this rapid increase and create functional libraries. Librarians have started to cooperate closely within the framework of ANKOS (Anatolian University Libraries Consortium) since 2000. ANKOS is one of the successful examples of library consortiums.